Acceptance of Nastar Substitution of Kepok Banana Flour - Ancella Maghfiroh Ihsmy; Sri Subekti; Sudewi Sudewi (Media Pendidikan Gizi dan Kuliner, 2023)
Nastar substitute for kepok banana flour is an innovative product from cookies or nastar pastries which are included in the type of molded cookies made from wheat flour which are then substituted with banana kepok flour. The purpose of this study was to obtain nastar recipes with banana kepok flour substitution and to find out consumer acceptance of kepok banana flour substitute nastar products. The method used in this study is an experimental method with product development starting from recipe analysis, product trials, to finding a reference recipe for making nastar with banana kepok flour substitution of 40%, 60% and 80%. Then, hedonic tests, QDA tests, and ranking tests were carried out by 3 expert panels to determine the best product samples. Furthermore, The samples were distributed to 30 consumer panelists who were randomly selected by means of a questionnaire based on 5 hedonic scales, namely strongly dislike, dislike, moderately like, like and really like. The results of the consumer hedonic test stated that nastar products were very liked and positively received by consumers.